2013
DOI: 10.1111/jocs.12055
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Strategies and Devices for Surgical Exclusion of the Left Atrial Appendage: A Word of Caution

Abstract: In patients with chronic atrial fibrillation, 90% of clots are located in the left atrial appendage (LAA). Therefore, LAA exclusion is a means of preventing thrombus formation and subsequent thromboembolic events in these patients. The LAA can be excluded from the systemic circulation via surgical, percutaneous, or thoracoscopic approaches. The surgical aim is complete obliteration of the appendage without a significant increase in either postoperative complications (bleeding, arrhythmias) or recurrence. We di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…Closure of the LAA is a well-established approach during arrhythmia surgery or with concomitant cardiac surgery [ 15 , 16 ]. Surgical LAA removal or closure performed during concomitant arrhythmia or mitral valve surgery was demonstrated to be feasible and safe by the LAAOS trial [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Closure of the LAA is a well-established approach during arrhythmia surgery or with concomitant cardiac surgery [ 15 , 16 ]. Surgical LAA removal or closure performed during concomitant arrhythmia or mitral valve surgery was demonstrated to be feasible and safe by the LAAOS trial [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Surgical LAA closure has been performed to prevent thromboembolic events during valve surgery and coronary artery bypass grafting or, more recently, as an isolated procedure using a thoracoscopic approach, 3,4) because most of the atrial thrombi are seen within the LAA.…”
Section: Discussionmentioning
confidence: 99%
“…Surgical LAA closure has been performed to prevent thromboembolic events during valve surgery and coronary artery bypass grafting or, more recently, as an isolated procedure using a thoracoscopic approach, 3,4) because most of the atrial thrombi are seen within the LAA. 3) Schwartz and colleagues 5) experimentally and clinically studied mechanisms of healing and intracardiac integration in LAA exclusion by a mechanical device and demonstrated that the excluded LAA filled with a thrombus early after exclusion, and that the thrombus subsequently organized over time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, a degree of thrombotic risk reduction has been achieved with techniques that modify the LAA anatomy to decrease thrombus formation ability. These techniques began with surgical methods to amputate the LAA or suture the LAA os closed [9,10], and thereby eliminate clots and the release of thrombi from the LAA into the central systemic circulation. These surgical approaches, although imperfect, have achieved some success, as discussed below.…”
Section: Thromboembolicmentioning
confidence: 99%